Severe constipation as the first clinical manifestation in multiple endocrine neoplasia type 2B: a case report and literature review - Lidan Zhang; Yan Guo; Lei Ye; Wenli Lu; Zhiya Dong; Wei Wang; Yuan Xiao (BMC Pediatrics, 2020)
Abstract Background The occurrence of multiple endocrine neoplasia type 2B (MEN2B) in Asians is very rare. In particular, patients with intractable constipation as the main clinical manifestation are even rarer. Atypical clinical manifestations are likely to lead to a diagnostic delay. In this report, we described a case of a delayed diagnosis of MEN2B, and the first clinical manifestation was intractable constipation. Case presentation A female teenager had suffered from intractable constipation since infancy. Because the colonoscopy and biopsy results from local hospitals did not confirm the presence of congenital megacolon, the girl had been followed up at a local clinic for a long time. The diagnosis was not confirmed until thyroid masses were found in the Pediatric Department of Shanghai Ruijin Hospital when she was 12 years old. According to our detailed evaluation, she suffered from Hirschsprung disease (HD), growth retardation, medullary thyroid carcinoma (MTC) and mucosal neuroma due to a mutation in the RET gene. Thus, the diagnosis of MEN2B was confirmed. Afterward, the girl underwent several surgeries and was still being followed up before the article was published. Conclusion MEN2B has atypical clinical symptoms in the early stage. Refractory constipation may be the only clinical manifestation that lasts for several years. Therefore, we recommend that early screening and gene sequencing should be performed for patients with severe constipation due to HD to determine the cause of the disease and to improve the survival outcome.